Retooling for growth : building a 21st century economy in America's older industrial areas - McGahey, Richard; Vey, Jennifer S. (Brookings Institution Press, 2008)
"Offers achievable strategies for revitalizing industrial areas and building upon the potential of overlooked resources of economic, physical, and cultural significance. Addresses such challenges as fostering entrepreneurship, reducing poverty and inequality, and augmenting the number of skilled professionals. Provides analysis of healthy economic development practices for public and private sectors"--Provided by publisher